Strategic Implications and Performance Outcomes in Mergers and Acquisitions: A Semantic Review - Deni Sunaryo; Abdul Fatah; Ardilla Putri; Nurkhasanah Ramadhani Azizah; Rhaisa Aulia Mustafani (Digital Innovation : International Journal of Management, 2025)
Mergers and acquisitions (M&A) are widely recognized as strategic instruments for corporate growth, restructuring, and competitive advantage. This semantic review synthesizes recent Scopus‑indexed literature to examine the strategic implications and performance outcomes of M&A. The study highlights that strategic alignment between acquiring and target firms is fundamental to synergy realization, operational efficiency, and innovation. Managerial expertise emerges as a decisive factor, with effective leadership ensuring smooth integration and long‑term value creation. Market dynamics, including economic volatility, regulatory changes, and geopolitical tensions, significantly influence M&A strategies and outcomes, while technological integration accelerates digital transformation and enhances competitive positioning. Cultural fit is identified as a critical determinant of organizational cohesion, with misalignment often leading to employee resistance and reduced productivity. Financial outcomes vary, ranging from profitability improvements through economies of scale to underperformance caused by overestimated synergies or poor integration. Furthermore, environmental, social, and governance (ESG) considerations are increasingly shaping M&A strategies, reinforcing stakeholder trust and sustainable value creation. By adopting a holistic approach that integrates strategic foresight, managerial acumen, market awareness, technological innovation, and sustainability, firms can optimize M&A as a tool for growth and resilience in dynamic global markets.